Complex regional pain syndrome after multiple revision total hip arthroplasty surgeries - Adam, Mahmoud Faisal (2023)
Persistent pain after total hip arthroplasty (THA) is a real concern for the surgeon and is a significant cause of patient dissatisfaction; periprosthetic joint infection (PJI), aseptic loosening, and instability are among the common causes of painful THA. However, few rare causes have been reported in the literature; the complex regional pain syndrome (CRPS) was reported to occur after primary hip and knee arthroplasties. Case presentation: We present a female patient who had bilateral hip resurfacing when she was 28 years old after being diagnosed with bilateral hip avascular necrosis; over 16 years, she was satisfied. She started developing pain in her right hip in 2019, diagnosed as aseptic loosening, and a revision using a cementless THA was performed. Six months later, she was diagnosed with PJI, which was treated in two stages; after the first-stage revision THA, the patient complained of persistent pain in her lower leg with a burning sensation and change in skin color, not responding to conservative lines...